Defect, temperature, and strain effects on lattice heat conductivity of egg-tray graphene. (14th April 2021) - Sun, Zhihui; Zhang, Jie; Wang, Hanxiao; Pan, Guangshan; Wang, Tianhua; Xie, Lu; Peng, Qing
Abstract: Micro and nano devices generally have the characteristics of high performance and compact size, so their own heat transfer and heat dissipation problems are becoming more and more serious. Therefore, it is necessary to clarify the heat transport mechanism in the micro–nano structure by analyzing the heat transport properties of nanomaterials, and then control the thermal conductivity of nanodevices. We have investigated the lattice heat transfer of egg-tray graphene using non-equilibrium molecular dynamics simulations. Three structures (I, II and III) are studied according to the number of hexagons as 10, 16, and 56 respectively. The increases of lattice thermal conductivity with an increase of length in sub-microns implies the large mean free path of phonons in egg-tray graphene, similar as that of graphene. The large-size-limit thermal conductivity is 43, 45, and 60 W m −1  K −1 for I, II, and III respectively, much smaller than that of graphene (393 W m −1  K −1 ) in our model. The thermal conductivity decreases with an increase of strain, as well as temperature. The heat transfer performance of structure-II is sensitive to both phonon modes and phonon quantities in compression, while in tension it is determined only by the phonon modes. Our results may be useful in thermal conductivity engineering and heat transfer management in egg-tray graphene.